2021
DOI: 10.1002/chem.202101004
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Directing Groups and Their Pivotal Role in C−H Activation

Abstract: Scheme 2. Amides derived from the acetylation of anilines used as directing group in metal-catalyzed CÀ H activations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 369 publications
(752 reference statements)
0
28
0
Order By: Relevance
“…In this process, various benzaldehydes as well as benzothiophene-and thiophene-3-carbaldehydes could be heteroarylated in moderate to good yields (Scheme 26). [54] As a note, the authors could observe that the substrates underwent a double CÀ H activation towards benzo [4,5]thieno [3,2-c]isoquinolines under the reaction conditions with a range of benzothiophenes when using βalanine as the transient directing mediator in HFIP.…”
Section: (Hetero)arylation Reactionsmentioning
confidence: 97%
See 3 more Smart Citations
“…In this process, various benzaldehydes as well as benzothiophene-and thiophene-3-carbaldehydes could be heteroarylated in moderate to good yields (Scheme 26). [54] As a note, the authors could observe that the substrates underwent a double CÀ H activation towards benzo [4,5]thieno [3,2-c]isoquinolines under the reaction conditions with a range of benzothiophenes when using βalanine as the transient directing mediator in HFIP.…”
Section: (Hetero)arylation Reactionsmentioning
confidence: 97%
“…In this context, the direct functionalization of C(sp 2 )À H bonds in arenes has received a great deal of attention over the last decades and still constitutes a challenge of utmost importance. [4,7,8] For arenes whose innate reactivity cannot be used for the selective functionalization of one of their C(sp 2 )À H bonds or to bypass this innate reactivity, the use of directing groups is usually the best option and has been extensively studied. In most cases however, the directing group needs to be installed and cleaved -whenever possible -in at least two separate steps, diminishing the attractiveness and utility of the overall process.…”
Section: C(sp 2 )à H Bond Functionalization Of Arenesmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7] The oxidative coupling of alkenes and arenes was originally discovered by Fujiwara and Moritani more than fifty years ago for Pd(II) catalysts. [8][9] The reaction lay dormant until the early 2000's when De Vries, van Leeuwen and co-workers found that benzoquinone is a suitable oxidant and that a catalyst-directing group (CDG) [10] facilitates the reaction and enables regioselectivity. [11] Our interest in this chemistry stems from earlier investigations into the dual use of acetamides as catalyst-directing groups in CÀ H-activation reactions and their subsequent traceless removal through the deacetylation-diazotation-coupling sequence (DDC-sequence) [12] previously developed in our group.…”
Section: Introductionmentioning
confidence: 99%